Students’ Perceptions of Using Schoology in E-learning: A Literature Review - Nugraha Kholid, Mohammad Fikri; Hastomo, Tommy (Universitas Islam Negeri Raden Intan Lampung, 2022)
Students in modern era need using technology very much in learning. Technology can assist teachers and students in finding and gathering information. In addition, technology can also be used to facilitate the distance learning process such as assignment collection and assessment. In distance learning, there are many technologies or tools that can be used by teachers and students, one of which is Schoology. Schoology is one of e-learning application where, students can take classes made by teachers / tutors through this application. Several classes can be created by the Teacher at once, each class chooses its own access code. The aim of this study is to analyze the effectiveness of the use of Schoology in e-learning, how the advantages and disadvantages of Schoology in e-learning. This study reports several main studies whose focus is relevant since the last five years ( Joshua et al., (2016); Sanchez Garcia et al., (2018), Rosalina (2018), Rama & Wahyudi (2019). The results showed that the students had positive perceptions of using Schoology.